Simultaneous reduction of nitrate and perchlorate by sulfide-based denitrification process - Calis, Bedia; Ucar, Deniz (Yildiz Technical Univ, 2023)
In this study, sulfide-based denitrification was used for the first time for perchlorate reduction. Perchlorates (CIO4-) are the salts obtained from perchloric acid and are widely used in missile and rocket systems as well as in the automotive industry, fireworks production and some pharmaceutical industries (in the treatment of hyperthyroidism). Perchlorate prevents the iodine uptake of the thyroid gland and inhibits the production of thyroid hormones (triiodothyronine-T3 and thyroxine-T4). Autotrophic reduction methods are gaining popularity in the removal of perchlorate, which is often found together with nitrate in water. In this study, sulfide produced in an ethanol-based sulfidogenic reactor was used for simultaneous reduction of nitrate, nitrite and perchlorate. The study was conducted with batch reactors in 196 hours with varying concentrations of nitrate, nitrite and perchlorate in the presence of 30 mg/L total sulfide. The study showed that the perchlorate removal rate was gradually reduced in reactors containing 10 mg/L nitrite, 10 mg/L nitrate and 20 mg/L nitrite and 20 mg/L nitrate, respectively. The control group reactors revealed that sulfide is used as an electron donor and the process is biological. It was observed that sulfide, a dissolved inorganic sulfur compound, can reduce perchlorate in the presence of nitrate and/or nitrite, and the reduction rate is largely dependent on the presence of nitrate and nitrite.
Keywords: Nitrite Reduction; Nitrate Reduction; Perchlorate Reduction; Sulfide-Based Reduction; Water Treatment